2021
DOI: 10.5423/ppj.oa.04.2021.0059
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Plant-Parasitic Nematodes of Turfgrass in Korea

Abstract: Plant-parasitic nematodes are not only an important constraint on agricultural crop production, but also cause both direct and indirect damage to turfgrass, which is a ground cover plant. However, studies on plant-parasitic nematodes of turfgrass in Korea are scarce. A survey for plant-parasitic nematodes was carried out on 13 golf courses in Korea. The results yielded 28 species/taxa belonging to 16 genera and 12 families of plant-parasitic nematodes. Among the isolated species, Helicotylenchus microlobus, Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Prior to this work, there have been several research papers illustrating a broad diversity of nematodes associated with turfgrasses in the United States [5,10,11,28,62], Canada [7,63,64], Argentina [65], Germany, Sweden, Norway [66,67], Belgium [8], Israel [68] and Korea [6]. Previous research showed that the species of Hemicriconemoides and Tylenchorynchus associated with turfgrasses include H. chitwoodi Esser, 1960 and H. wessoni Chitwood & Birchfield, 1957 in Cynodon dactylon [10,11]; H. brachyurus (Loos, 1949) Chitwood & Birchfield, 1957 in Poa pratensis and Zoysia japonica [6]; T. claytoni Steiner, 1937 in P. pratensis and Z. japonica [6,10,11]; T. dubius in Agrostis stolonifera and P. pratensis [69]; T. annulatus in Z. japonica; and T. thermophilus in Z. japonica and P. pratensis [6]. The work presented here provides new records of H. rosae and T. leviterminalis associated with turfgrasses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to this work, there have been several research papers illustrating a broad diversity of nematodes associated with turfgrasses in the United States [5,10,11,28,62], Canada [7,63,64], Argentina [65], Germany, Sweden, Norway [66,67], Belgium [8], Israel [68] and Korea [6]. Previous research showed that the species of Hemicriconemoides and Tylenchorynchus associated with turfgrasses include H. chitwoodi Esser, 1960 and H. wessoni Chitwood & Birchfield, 1957 in Cynodon dactylon [10,11]; H. brachyurus (Loos, 1949) Chitwood & Birchfield, 1957 in Poa pratensis and Zoysia japonica [6]; T. claytoni Steiner, 1937 in P. pratensis and Z. japonica [6,10,11]; T. dubius in Agrostis stolonifera and P. pratensis [69]; T. annulatus in Z. japonica; and T. thermophilus in Z. japonica and P. pratensis [6]. The work presented here provides new records of H. rosae and T. leviterminalis associated with turfgrasses.…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys of nematodes associated with turfgrasses have been conducted in the USA and other countries, and have shown a broad diversity with different countries and regions [5][6][7][8][9][10][11]. In Florida, USA, common genera of nematodes that damage turf include ectoparasitic Belonolaimus, Trichodorus, Nanidorus, Helicotylenchus and Mesocriconema, and endoparasitic Hoplolaimus and Meloidogyne [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subbotin et al recorded that H. microlobus was collected in California, Illinois, and Iowa, in the United States of America and in several European countries, including Spain, Italy and Russia [ 18 ]; Yan et al reported H. microlobus infecting soybean in North Dakota [ 19 ]. Abraham and Dong reported H. microlobus in turfgrass in Korea [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Helicotylenchus pseudorobustus and Meloidogyne naasi were the most prevalent nematodes. Twenty-eight species/taxa belonging to 16 genera in 12 families of PPNs were found at 13 golf courses in Korea [ 11 ], with Helicotylenchus microlobus , Mesocriconema nebraskense , Tylenchorhynchus claytoni , Mesocriconema sp., and Meloidogyne graminicola the most prevalent species in all management zones [ 11 ]. Twenty-three nematode genera are known to be associated with turfgrasses in Australia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%